DAMPAK KEGIATAN PT. ANEKA TAMBANG TERHADAP PENDAPATAN MASYARAKAT - Zam Zam, Muhajir (Green Earth, 2012)
Halmahera Timur district is one of North Maluku Provincie districts having a huge potential of natural resources. One of them is nickel. Mining and quarry sectors constribute  17.66 % of the gross domestik regional income (PDRB) in Halmahera Timurdistrict. Is that any impact of PT. Antam activities  on income of the local community. The objective of this research was to find out inpacts of PT. Antam on income of localcommunity of Maba sub-district in Halmahera Timur district.This research was conducted in of maba sub-district, Halmahera Timur district North Maluku Provinci were  PT. Aneka Tambang is located. Data were gathered by interviewing 70 local respondents. Income education and level of emlpoyment data after the operation of PT. Antam wee collected during fieldwork. Income data was used as dependent variable. The were analysed using least squareRegresion/Ordinary least square with ioncome fungtion equals to F (level of education and employment). The results showed that level of education was statistically significant and positive to the improvement of local income in maba sub-district. Through coolporate Social responsibility(CSR) activities delivered by PT. Antam local people were provided with scholarship tocontinue their study. There fore, thre has been improvement in level of education of the local people. This  in the employment level and local income. How ever, it was found that job recruitment had no significant effects on level of local income. This is because not all local people work for PT. Antam. It  Can be concluded that improvement in local income had a significant effect on economic growth of all sector at at the and 2010. Economic growth of the district was 3.75 %. It is suggested that PT.Antam should inprove the company community development project especially in its education and health programs Key words: Impact, PT. Aneka Tambang, Incam